Diversity and genomics of giant viruses in the North Pacific Subtropical Gyre - Farzad, Roxanna; Ha, Anh D.; Aylward, Frank O. (Frontiers in Microbiology, 2022)
Large double-stranded DNA viruses from the phylum Nucleocytoviricota are ubiquitous members of marine ecosystems that are important agents of mortality for eukaryotic plankton. Although giant viruses are known to be prevalent in marine systems, their activities in oligotrophic ocean waters remain unclear. Oligotrophic gyres constitute the majority of the ocean, and assessing viral activities in these regions is therefore critical for understanding overall microbial processes in the ocean. In this study, we generated 11 metagenome-assembled genomes (MAGs) of giant viruses from samples previously collected from Station ALOHA in the North Pacific Subtropical Gyre. Phylogenetic analyses revealed that they belong to the orders Imitervirales (n=6), Algavirales (n=4), and Pimascovirales (n=1). Genome sizes ranged from ~119-574 kbp, and several of the genomes encoded predicted TCA cycle components, cytoskeletal proteins, collagen, rhodopsins, and proteins potentially involved in other cellular processes. Comparison with other marine metagenomes revealed that several have broad distribution across ocean basins and represent abundant viral community members in pelagic surface waters. Our work sheds light on abundant giant viruses present in oligotrophic ocean waters across the globe.